Intellectual capital and organisation culture : a dynamic resource model to organisation effectiveness / Amrizah Hj Kamaluddin - Hj Kamaluddin, Amrizah (2009)
Intellectual capital has been postulated as an essential element for firms survival and competitive advantages (Riahi-Belkaoui, 2003). Competitive success of businesses is depending more on strategic management of intellectual capital and less on the strategic allocation of physical and financial resources. The Resource-Based Theory views that firm resources such as intellectual capital are the key drivers of competitive advantages and vital to firm financial performance (Riahi-Uelkaoui, 2003). Nevertheless, in a different economic set up where there exists different technological advancements (Chen et al., 2005) and differences in views on the metaphors of knowledge between the West and Asia (Andriessen and Boom, 2007), a different implication of intellectual capital may exist. Thus, the research contributes to the intellectual capital literature of the ASEAN countries where culture, politics, economics and social environment provide different perspectives and challenges.